Pengukuran Kualitas Pelayanan Terhadap Kepuasan Pembuatan Paspor - Pioner Pelawi; Nasrul Efendi; Sugianta Ovinus Ginting (Jurnal Wira Ekonomi Mikroskil, 2022)
The focus of the study aims to determine and analyze the ability of service quality to affect the satisfaction of passport making at the Class I Immigration Office Polonia Medan. The population in this study is people who make passports, both for new applications and extensions, the number of which is not known with certainty. The formula used in determining the number of samples refers to the Lameshow formula so that a total sample of 96 respondents is obtained. The sampling technique used is non-probability sampling with an accidental approach. Testing data used include simple linear regression analysis, t test and coefficient of determination (R²). The results showed that the quality of service affects the satisfaction of making passports at the Immigration Office Class I TPI Polonia Medan with a coefficient of determination (R²) of 0.374 which means that service quality ability is only able to explain variations in the formation of passport making satisfaction of 37.4% while the remaining 62 ,6% was formed by other variables not examined. Suggestions for the continuation of research that aims to determine other variables that play a role in realizing satisfaction in making passports should be expanded by adding other variables such as facilities.